Paediatric Eyelid Lesions- A Report of 20 Cases - Sathe, Pragati; Asthana, Ankita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Eyelid lesions are one of the commonest lesions encountered by ophthalmologists in their clinical practice. They could be classified in various ways such as neoplastic or non-neoplastic; congenital or acquired. The common benign conditions affecting the eyelid include cysts like dermoid, epidermoid and epithelial cysts, inflammatory lesions, melanocytic nevi and papilloma. Ignorance about the benign nature of the lesion may lead to increased debility. The purpose of this study is to contribute information to the literature on various eyelid lesions and their incidence as found in a tertiary hospital. Methods: This is a retrospective observational study of surgically excised eyelid lesions in patients below 12 years of age. The study was conducted after obtaining permission from the Institutional Ethics Committee. Result: Out of 20 lesions, 15 cases belonged to the non-neoplastic category while five cases were neoplastic in nature. Cystic lesions predominated in the non-neoplastic category (11 out of 15 cases). The remaining four cases in the non-neoplastic category included three cases of infective etiology and one case of developmental etiology. There were no malignant neoplasms found in our study. The common presenting feature was that of eyelid swelling. Highest incidence of eyelid lesions was in the upper lid (14 of 20 cases, i.e. 66.66%). Conclusion: It is necessary to subject every lesion of the eyelid to histopathological examination. Sometimes, clinically benign lesions turn out to be malignancies which entails a wider surgery later. This study points out to the wide spectrum of lesions that can afflict the eyelid.